coating liquid
Patent Information
- Application Number
- JP2022059255
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-31
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-03-31
Abstract
Description
[Technical Field]
[0001] This invention relates to a photocatalytic coating solution. [Background technology]
[0002] Because titania, a photocatalyst, has a high refractive index, it scatters a lot of light, and coatings made with titania tend to become cloudy. Therefore, in order to obtain a highly transparent coating, it is essential to use titania nanoparticles with small particle sizes, but the smaller the particle size, the higher the cohesiveness, making it difficult to obtain a highly uniform coating.
[0003] Furthermore, titania nanoparticles generally have poor adhesion because they are only in contact with the substrate. Therefore, a binder, which is an auxiliary component, is necessary when converting titania into a paint.
[0004] Such binders require not only normal applicability, adhesion, and crack resistance, but also transparency that allows light to pass through and resistance to degradation from photocatalytic activity. Therefore, ordinary binders cannot be used, and fluororesins, silica sols, or polysiloxanes, which have high bond energy and are difficult to decompose, are often used (for example, Non-Patent Document 1).
[0005] However, fluororesins have poor affinity for hydrophilic titania, making it difficult to create a transparent coating solution.
[0006] Furthermore, increasing the amount of silica added increases its interaction with titania, impairing transparency and liquid stability, and making it more prone to gelation. Also, since both titania and silica are particles, their adhesion to the substrate and crack resistance do not improve.
[0007] Furthermore, among organopolysiloxane compounds that are expected to be more flexible than silica, silicone-based materials that have two organic groups (here, organic groups refer to methyl groups and phenyl groups, and do not include alkoxy groups that undergo hydrolysis and release organic components) are excellent in terms of flexibility, coatability, and transparency, but this also means that the surface of titania is coated, and the photocatalytic activity is greatly reduced.
[0008] Similarly, Patent Document 1 discloses a siloxane compound having one organic group as a binder, but if the amount added is small, it does not function as a binder, and if the amount added is large, the photocatalytic activity decreases, similar to silicone-based systems.
[0009] The binder needs to have affinity for titania, and in addition, it must possess many physical properties such as the time-dependent stability of the liquid when mixed with titania, transparency, non-inhibition of photocatalytic activity, crack resistance, and adhesion to the substrate. Therefore, finding a suitable one is difficult. Furthermore, low-temperature curing properties are desirable to increase versatility. [Prior art documents] [Patent Documents]
[0010] [Patent Document 1] International Publication No. 96 / 029375 [Non-patent literature]
[0011] [Non-Patent Document 1] Tetsuo Yoshimoto, "New Developments in Photocatalytic Films: Immobilization Methods for Photocatalysts," Surface Technology 50.3(1999):242-246. [Overview of the project] [Problems that the invention aims to solve]
[0012] In view of the circumstances as described above, an object of the present invention is to provide a coating liquid for obtaining a coating film that has high affinity with a photocatalyst, maintains transparency, does not impair the photocatalytic effect, is excellent in crack resistance and adhesion, cures at low temperature, and is also excellent in temporal stability even when mixed with an aqueous dispersion. [MEANS FOR SOLVING THE PROBLEMS]
[0013] As a result of repeated intensive studies by the present inventors to solve the above problems, it has been found that the above problems can be solved by using a coating liquid containing predetermined titanium oxide nanoparticles, amorphous silica, and a solvent. The present inventors have further conducted studies on the basis of such findings, and have completed the present invention.
[0014] That is, the present invention provides the following coating liquid. Item 1. Containing titanium oxide nanoparticles, amorphous silica, water, and alcohols having 4 or less carbon atoms, The titanium oxide nanoparticles have acetoxy groups bonded to the surface, a mass reduction rate at 200°C or higher when heated to 600°C by a simultaneous differential thermogravimetric analyzer is 5 mass% or more, and have an average particle diameter of 1 to 10 nm, The coating liquid, wherein the amorphous silica has a residual acid content of 100 ppm or less, a residual organic group content of 5 to 35 mass%, and an average particle diameter of 50 nm or less. Item 2. The mass of the titanium oxide nanoparticles (M T ) relative to the mass of the amorphous silica (M A ) in mass ratio (M A / M T ) is 0.1 to 2.0, the coating liquid according to Item 1. Item 3. The alcohols are at least one selected from the group consisting of methanol, ethanol, 1-propanol, 2-propanol, 2-butanol and tert-butyl alcohol, The coating liquid according to item 1 or 2, wherein the mass of the alcohols contained in the coating liquid is 10 mass% or more, with the total mass of the water and the alcohols being 100 mass%. Item 4. A coating film formed by the coating liquid according to any one of items 1 to 3. Item 5. An antibacterial agent or antiviral agent produced using the coating liquid according to any one of items 1 to 3.
Effects of the Invention
[0015] According to the coating liquid of the present invention configured as described above, it is possible to obtain a coating that has high affinity with a photocatalyst, maintains transparency, does not impair the photocatalytic effect, has excellent crack resistance and adhesion, cures at low temperature, and also has excellent temporal stability even when mixed with an aqueous dispersion.
Modes for Carrying Out the Invention
[0016] In the present specification, "contain" is a concept that encompasses all of "comprise", "consist essentially of", and "consist of". In addition, in the present specification, when a numerical range is indicated by "A to B", it means A or more and B or less.
[0017] In the present specification, "low-temperature curability" means being capable of being cured at a low temperature of 10 to 100°C.
[0018] In the present specification, "photocatalytic activity" means a collective term for the properties possessed by a photocatalyst, such as hydrophilicity, organic matter decomposition performance, antibacterial and antiviral performance, and the like.
[0019] (1. Coating liquid) The coating liquid of the present invention comprises titanium oxide nanoparticles, amorphous silica, water, and alcohols having 4 or less carbon atoms.
[0020] (1.1. Titanium oxide nanoparticles) In this specification, "titania," "titanium dioxide," and "titanium oxide" include not only titanium dioxide (TiO2) but also titanium trioxide (Ti2O3), titanium monoxide (TiO), Ti4O7, Ti5O9, and other compositions that are oxygen-deficient compared to titanium dioxide. Furthermore, it also includes those having groups other than Ti-O-Ti, such as terminal OH groups, which are a result of the synthesis of some titanium dioxide. In addition, it also includes those in which organic acids, etc., are bonded to terminal OH groups.
[0021] In titanium oxide nanoparticles, acetoxy groups are bonded to at least some of the titanium atoms present on the surface. Normally, water, inorganic acids, and free organic acids are almost completely volatile below 200°C. On the other hand, in the titanium oxide nanoparticles used in this invention, since acetoxy groups are bonded to at least some of the titanium atoms present on the surface, they gradually desorb in the range of 200 to 600°C. Specifically, they gradually desorb in the range of 200 to 600°C, with a peak at approximately 260°C.
[0022] Thus, because the titanium oxide nanoparticles used in this invention have acetoxy groups bonded to at least some of the titanium atoms on their surface, aggregation of titanium oxide particles is suppressed during drying or firing, making them less prone to cracking and peeling, resulting in particularly excellent coatability and transparency, and consequently, excellent photocatalytic activity. In other words, if acetoxy groups are not bonded to at least some of the titanium atoms on the surface of the titanium oxide nanoparticles, sufficient coatability and transparency of the coating cannot be obtained.
[0023] While it is generally common knowledge that the presence of an acetoxy group reduces photocatalytic activity, the coating liquid of the present invention, as described above, has particularly excellent crack and peeling suppression effects, and therefore, despite having an acetoxy group, can also improve photocatalytic activity.
[0024] Furthermore, it is preferable that titanium oxide nanoparticles have a large number of acetoxy groups bonded to the titanium atoms present on their surface. When acetoxy groups are present on at least some of the titanium atoms on the surface, they gradually detach in the range of 200 to 600°C as described above, resulting in a large mass loss rate above 200°C when heated using a differential thermogravimetric analyzer (TG-DTA). In other words, in this invention, the mass loss rate above 200°C when heated using a differential thermogravimetric analyzer (TG-DTA) represents an indicator of the number of acetoxy groups bonded to the titanium atoms present on the surface.
[0025] Therefore, when heated to 600°C using a differential thermogravimetric analyzer (TG-DTA), the mass loss rate above 200°C is 5% by mass or more, and preferably 7-20% by mass. The above mass loss rate represents the mass loss rate of titanium oxide nanoparticles at 600°C relative to the mass at 200°C during the heating process. In this case, the detailed conditions for the differential thermogravimetric analyzer (TG-DTA) are: atmosphere: air, heating rate: 3°C / min. However, if the intention is simply to achieve an antifouling effect due to hydrophilicity, or if high transparency is not required, titanium oxides with a mass loss rate outside the above range can also be used.
[0026] The average particle size of titanium oxide nanoparticles is preferably 1 to 10 nm, and more preferably 0.5 to 6 nm, from the viewpoint of transparency, coatability, hydrophilicity, and photocatalytic activity. Normally, when the average particle size is small, shrinkage during heating is large, making cracking and delamination from the substrate more likely. However, in this invention, titanium oxide exhibits excellent coatability despite its small average particle size. The average particle size of the titanium oxide is measured by electron microscopy (TEM). Note that if the intended purpose is simply to achieve an antifouling effect due to hydrophilicity, or if high transparency is not required, titanium oxide with an average particle size outside the above range can also be used.
[0027] The specific surface area of titanium oxide nanoparticles is 95-500 m², taking into consideration transparency, coatability, hydrophilicity, and photocatalytic activity. 2It is preferable to use / g, and 200-400m 2 It is more preferable to use the value per gram ( / g). The specific surface area of titanium oxide is measured by the BET method. In cases where the intention is simply to achieve an antifouling effect due to hydrophilicity, or when high transparency is not required, titanium oxides with a specific surface area outside the above range can also be used.
[0028] Furthermore, the titanium oxide nanoparticles may contain N, Cl, and S elements at concentrations of 0 to 5000 ppm, more preferably 0 to 1000 ppm, respectively. By setting the concentrations of N, Cl, and S elements in the titanium oxide nanoparticles within this range, corrosion of the substrate is more easily suppressed.
[0029] The above composition means that impurities derived from acidic titania precursors such as TiCl4 and TiOSO4 are absent or present in very small amounts. The concentrations of N, Cl, and S elements in the above titanium oxide can be measured by WDX (X-ray fluorescence).
[0030] As described above, the titanium oxide nanoparticles have acetoxy groups bonded to at least some of the titanium atoms present on their surface, and it is preferable that these acetoxy groups are represented by -OCOCH3 and bonded to the titanium atoms.
[0031] Furthermore, the crystalline form of the above-mentioned titanium oxide nanoparticles is preferably anatase. By adopting the anatase form, it becomes easier to improve the photocatalytic activity. Also, for the same reason, it is preferable that there are no crystalline forms other than anatase, and that it be 100% anatase form.
[0032] These titanium oxide nanoparticles have adjustable average particle size and specific surface area, and exhibit excellent dispersibility, resulting in superior transparency and coatability. Furthermore, these titanium oxide nanoparticles also possess excellent photocatalytic activity.
[0033] The titanium oxide nanoparticles mentioned above are, for example, (A) A step of mixing a titanium-containing substance, acetic acid and water to obtain a dispersion, (B) The process comprises heating the dispersion obtained in step (A) at a temperature higher than 80°C for at least one hour, and In step (A) above, the mixing ratio of the titanium-containing substance and the acetic acid can be obtained by a method in which the amount of acetoxy groups in the acetic acid is 1 mole or more per mole of titanium in the titanium-containing substance.
[0034] In step (A), a dispersion is obtained by mixing a specific amount of a substance containing titanium, a specific amount of acetic acid, and water.
[0035] There are no particular restrictions on the titanium-containing substances used, as long as they become titanium oxide (titanium dioxide) upon heating. In other words, titanium dioxide and / or titanium dioxide precursors are preferred as titanium-containing substances, and specifically include titanium dioxide; titanium hydroxide; titanium alkoxide; titanium halides such as titanium trichloride and titanium tetrachloride (especially those neutralized with a base); and metallic titanium. These titanium-containing substances can be used individually or in combination of two or more.
[0036] Among these, titanium alkoxide, titanium hydroxide, or titanium halide (especially those neutralized with a base) are preferred from the viewpoint of the dispersibility, coatability, hydrophilicity, and photocatalytic activity of the resulting titania, and titanium alkoxide is more preferred from the viewpoint of purity, dispersibility, coatability, hydrophilicity, and photocatalytic activity.
[0037] Examples of titanium alkoxides include titanium tetraisopropoxide, titanium tetra-n-butoxide, titanium tetra-n-propoxide, and titanium tetraethoxide. From the viewpoint of cost, water solubility of by-products, applicability, hydrophilicity, and photocatalytic properties, titanium tetraisopropoxide is preferred.
[0038] Furthermore, depending on the combination of titanium alkoxide and acetic acid, the resulting titanium oxide may act as a catalyst to release ester compounds that are poorly soluble in water. While titania itself poses no problem (for example, in the combination of titanium tetra-n-butoxide and acetic acid, butyl acetate is formed and released when mixed and heated), from the viewpoint of obtaining a homogeneous dispersion, it is preferable to use a combination of an organic acid and titanium alkoxide that yields an organic acid alkoxide with excellent water solubility.
[0039] For titanium halides (titanium tetrachloride, titanium trichloride, etc.), it is preferable to neutralize them with a base and wash the precipitate before use, from the viewpoint of impurities (halogens), corrosion of reactors during mass production, crystallinity control, coating properties, hydrophilicity, and photocatalytic properties. In that case, it is preferable to use the resulting titanium oxide without drying it, from the viewpoint of dispersibility.
[0040] When using solids such as titanium dioxide or metallic titanium, the average particle size of the titanium dioxide powder or metallic titanium powder is preferably 100 nm or less, and more preferably 50 nm or less. There is no specific lower limit, but it is usually around 1 nm. If the particle size is large, it can be used after being pulverized dry or wet using a planetary ball mill or paint shaker. The average particle size of solids such as titanium dioxide and metallic titanium is measured by electron microscope (SEM or TEM) observation.
[0041] The concentration of the titanium-containing substance in the dispersion is preferably 0.01 to 5 mol / L, and more preferably 0.05 to 3 mol / L, from the viewpoint of productivity, viscosity of the reaction solution, coatability, hydrophilicity, and photocatalytic activity.
[0042] From the viewpoints of dispersibility, applicability, hydrophilicity, photocatalytic properties, and cost, it is preferable to adjust the amount of acetic acid used so that it contains 1.5 moles or more, preferably 2 moles or more, of carboxyl groups per mole of titanium in the titanium-containing material. The more acetic acid is used, the better the long-term stability and applicability. There is no particular upper limit, but it is usually 4 moles per mole of titanium in the titanium-containing material.
[0043] The concentration of acetic acid in the dispersion is preferably 0.02 to 10 mol / L, and more preferably 0.1 to 7 mol / L, from the viewpoint of dispersibility, coatability, hydrophilicity, photocatalytic properties, and cost.
[0044] As the reaction solvent, it is preferable to use an aqueous solvent such as water as the main component (specifically, for example, 50% by mass or more), but it may also contain alcohol or ester during the reaction.
[0045] For example, when titanium tetraisopropoxide is used as a raw material, isopropanol is produced by reaction with acetic acid. Isopropyl acetate may also be produced by heating. In other words, alcohol or ester may be added to the dispersion obtained in step (A), or it may be generated in the system. This alcohol or ester may be removed by heating in an open system below 100°C, by reducing the pressure, or it may remain in the reaction solution.
[0046] Furthermore, if alcohol is present in the dispersion, the average particle size of the resulting titanium oxide tends to decrease. Therefore, alcohol may be intentionally added to control the average particle size.
[0047] In this invention, inorganic acids (especially strong inorganic acids) such as nitric acid, hydrochloric acid, and sulfuric acid, which are commonly used in the hydrothermal synthesis reaction of titanium oxide, can easily result in an anatase crystal form of the obtained titanium oxide, and also provide excellent storage stability. However, these inorganic acids (especially strong inorganic acids) accelerate corrosion of the equipment, and are preferable to avoid from the viewpoint of impurities and wastewater. However, if it is necessary to improve the dispersibility and uniformity of the raw materials and facilitate handling, they can be used auxiliaryly in a range of, for example, 0.01 mol / L or less, as long as the effect is not impaired. In this case, the concentrations of N, Cl, and S elements in the dispersion will all be 0.01 mol / L or less.
[0048] The pH of the dispersion obtained in the above step (A) is preferably between 2 and 6, and more preferably between 2.1 and 5, taking into consideration the corrosion of the equipment, safety of handling, and dispersibility.
[0049] There are no particular restrictions on the method for preparing the dispersion in step (A). The titanium-containing substance, organic acid, and water (solvent) may be mixed simultaneously or sequentially. In particular, it is preferable to add the titanium-containing substance while stirring after mixing the acetic acid and water (solvent) to prevent aggregation and the formation of large clumps and to allow for continued stirring.
[0050] In step (B), the dispersion obtained in step (A) is heated at a temperature higher than 80°C for at least one hour.
[0051] Step (B) may be carried out under normal pressure or under pressure in a sealed container. However, in order to reduce the average particle size of the titanium oxide nanoparticles, it is preferable to carry out the step under normal pressure, specifically 0.09 to 0.11 MPa. When carrying out the step under pressure, it is preferable to carry out the reaction for a short time (for example, about 5 to 30 minutes) at 0.2 MPa or less (0.11 to 0.2 MPa) in order to facilitate the formation of a film with high photocatalytic activity and high transparency.
[0052] During heating, stirring is preferable to ensure sufficient reaction between the titanium-containing substance, acetic acid, and water. There are no particular restrictions on the stirring method, and conventional methods can be followed. Furthermore, the stirring time is preferably 1 hour or more, and more preferably 1.5 hours or more, from the viewpoint of ensuring sufficient reaction between the titanium-containing substance, acetic acid, and water. There is no particular upper limit on the stirring time, but it is usually 240 hours.
[0053] From the viewpoint of coatability and crack resistance, the heating temperature is preferably above 80°C, and more preferably above 82°C. However, there is no particular upper limit to the heating temperature; for example, when reacting at atmospheric pressure, it is usually 120°C.
[0054] The pH of the dispersion obtained in such a process (B) is preferably between 2 and 6, and more preferably between 2.1 and 5, taking into consideration the corrosion of the equipment, safety of handling, and dispersibility.
[0055] After step (B), the titanium oxide nanoparticles can be recovered by conventional methods such as precipitation and centrifugation. On the other hand, considering the method for producing the coating solution described later, it is preferable to use the obtained dispersion as is without performing isolation steps such as precipitation and centrifugation.
[0056] The concentration of the titanium oxide nanoparticles described above is preferably 0.01 to 3% by mass, more preferably 0.02 to 2.5% by mass, and even more preferably 0.05 to 1.5% by mass, based on 100% by mass of the total amount of the coating solution of the present invention, from the viewpoint of coatability, transparency, film strength, and photocatalytic activity. When using multiple types of titanium oxide nanoparticles, it is preferable to adjust the total amount so that it falls within the above range. Note that the TiO2 equivalent concentration is the concentration assuming that the titanium oxide is calcined to produce an equivalent amount of TiO2, and is not affected by the molecular weight of the organic group (acetoxy group) that the titanium oxide possesses.
[0057] Furthermore, in the coating solution of the present invention, the blending ratio of the organopolysiloxane compound to the titanium oxide is preferably 0.1 to 1, more preferably 0.2 to 0.8, and even more preferably 0.25 to 0.75 as an SiO2 / TiO2 equivalent mass ratio. Note that the TiO2 / SiO2 equivalent mass ratio is the blending ratio assuming that the organopolysiloxane compound and the titanium oxide are calcined to obtain equivalent molar amounts of SiO2 and TiO2, and is not affected by the molecular weight of the organic groups of the organopolysiloxane compound, the hydrolysis and condensation state of the terminal alkoxy groups, or the molecular weight of the organic groups (acetoxy groups) of the titanium oxide.
[0058] Generally, a higher TiO2 / SiO2 equivalent mass ratio tends to increase photocatalytic activity, while a lower ratio tends to increase coatability, transparency, film strength, etc. On the other hand, in the present invention, sufficient photocatalytic activity is achieved even with a low TiO2 / SiO2 equivalent mass ratio, and sufficient coatability, transparency, film strength, crack resistance, and adhesion are achieved even with a high TiO2 / SiO2 equivalent mass ratio.
[0059] (1.2. Amorphous Silica) In this specification, amorphous silica is defined as General Silane alkoxide, a silica precursor, or its linear It should be distinguished from polymers. In the case of tetraalkoxides, there are four or more carbon atoms per silicon atom, and in the case of trialkoxides, there are three or more carbon atoms per silicon atom (in most cases, the remaining functional groups are organic groups, so there are four or more). Even in oligomers, which are low molecular weight polymers of tetraalkoxides, two or more carbon atoms remain per silicon atom. For example, in the case of a decamer formed by the linear condensation of tetramethoxysilane Si(OCH3)4, there are 22 carbon atoms for every 10 silicon atoms, and the molecular weight is 1107. If this is completely hydrolyzed and dehydrated, it becomes 10SiO2, and the molecular weight is equivalent to 601. In other words, if the loss on heating is attributed to organic groups (when the alkoxy group hydrolyzes before condensation, the alcohol is eliminated before the water is eliminated, so the two cannot be separated), it can be considered that 45.7% by mass is contained in organic groups, and when actually calcined at 600°C or higher, the residue can be expected to be 54.3% by mass. In contrast, the amorphous silica used in the present invention has undergone sufficient hydrolysis and dehydration condensation, and the heat loss that can be considered as residual organic groups is 5% by mass or more and 35% by mass or less. It has more organic groups on its surface than silica nanoparticles, and fewer organic groups on its surface than the silane alkoxides and their oligomers mentioned above. Furthermore, the heat loss that can be considered as residual organic groups is preferably 7% by mass or more and 35% by mass or less, and more preferably 10% by mass or more and 35% by mass or less.
[0060] Furthermore, residual acid in amorphous silica promotes bonding between silica particles or between silica and titania, inhibiting the stability of the solution. Additionally, if the residual acid is a strong acid such as hydrochloric acid, it may corrode the substrate. Therefore, the residual acid content is preferably 100 ppm by mass or less, preferably 85 ppm by mass or less, and more preferably 50 ppm by mass or less. If the residual acid content exceeds 100 ppm by mass, gelation or heterogeneity of the silica-titania solution is likely to occur. Alternatively, a high residual acid content of a strong acid may cause corrosion of the substrate. There is no particular lower limit for the residual acid content; for example, it can be 0 ppm by mass.
[0061] In the case of silica, the average particle size is lower than that of titania because its refractive index is lower, and it is less likely to cause clouding even at the same particle size. Therefore, to achieve transparency, the average particle size of amorphous silica can be larger than that of titania nanoparticles. Considering the above, the average particle size of amorphous silica is 50 nm or less, and preferably 30 nm or less. There is no particular limit to the lower limit of the average particle size; for example, it can be 1 nm.
[0062] (1.3. Water and alcohols with 4 or fewer carbon atoms) The coating solution of the present invention further contains water and alcohols having 4 or fewer carbon atoms.
[0063] There are no particular restrictions on the type of water used; various types of water such as distilled water, tap water, industrial water, ion-exchanged water, deionized water, pure water, and electrolyzed water can be used. However, distilled water, ion-exchanged water, deionized water, and pure water are preferred because the positively charged anions may hinder the dispersion of titanium oxide nanoparticles.
[0064] The water content is preferably 5 to 65% by mass, more preferably 10 to 60% by mass, and even more preferably 15 to 55% by mass, based on the total amount of water and alcohols having 4 or fewer carbon atoms being 100% by mass. By setting the water content to 5% by mass or more, based on the total amount of water and alcohols having 4 or fewer carbon atoms being 100% by mass, sufficient dispersibility of titanium dioxide nanoparticles, which have a high affinity for water, can be obtained. Furthermore, by setting the water content to 65% by mass or less, aggregation of amorphous silica can be suppressed, and the occurrence of precipitation or turbidity in the coating solution can be suppressed, thereby improving the applicability and transparency of the coating solution.
[0065] Since titania has a high affinity for water and amorphous silica has a high affinity for organic solvents, it is preferable to use an organic solvent with high hydrophilicity. Therefore, the optimal ratio for dispersibility and transparency of water and organic solvents varies depending on the ratio of titania to amorphous silica.
[0066] As organic solvents, alcohols with four or fewer carbon atoms are used. Examples of such alcohols include monohydric alcohols such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, sec-butyl alcohol, and tert-butyl alcohol; and polyhydric alcohols such as ethylene glycol, propylene glycol, and glycerin. Examples of ethers include ethylene glycol monomethyl ether, propylene glycol monomethyl ether, ethylene glycol dimethyl ether, propylene glycol dimethyl ether, 3-methoxy-1,2-propanediol, 1,3-dimethoxy-2-propanol, and trimethoxymethane. Examples of ketones include acetylacetone. These organic solvents can be used individually or in combination of two or more.
[0067] Among the above, methanol, ethanol, 1-propanol, 2-propanol, 2-butanol, and tert-butyl alcohol are preferred.
[0068] Furthermore, considering the safety when applying the coating liquid of the present invention and its affinity with titania, it is preferable to include at least ethanol. For this reason, in the present invention, with the total amount of alcohols having 4 or fewer carbon atoms being 100% by mass, it is preferable to include 50 to 100% by mass of ethanol, and more preferably 60 to 100% by mass.
[0069] However, when the titania concentration is low (specifically, less than 1% by mass), the tolerance for organic solvents increases, and even if it contains a large amount of organic solvents other than ethanol, such as 2-propanol or 1-propanol, it will disperse sufficiently uniformly. Also, methanol may be used as the main component if there are no safety concerns during use.
[0070] (1.4. Other ingredients) The coating liquid of the present invention may also preferably contain other components, to the extent that it does not impair its effects and purpose. Such components are not particularly limited, and metal ions (e.g., silver, copper, iron, nickel, manganese, chromium, tin, niobium, vanadium, tantalum, tungsten, molybdenum, etc.), metal nanoparticles (e.g., silver, copper, gold, platinum, etc.), or organic substances (various deodorants, antibacterial agents, antiviral agents) may be added, taking into consideration deodorizing properties, antibacterial properties, antiviral properties, and visible light responsiveness, to the extent that they do not impair the uniformity of the liquid, the transparency of the coating film, and the long-term stability of the liquid. From the viewpoint of the long-term stability of the liquid, it is preferable to add metal nanoparticles that are insoluble in water and organic solvents.
[0071] (2. Method for manufacturing the coating solution) The method for producing the coating solution of the present invention is not particularly limited, and it can be obtained by adding titanium oxide nanoparticles to an amorphous silica dispersion. Alternatively, considering the transparency, photocatalytic activity, crack resistance, and adhesion of the coating, it can be produced by first producing an amorphous silica dispersion and a titanium oxide nanoparticle dispersion as described above, and then mixing these two solutions, or a mixture of these three solutions with a solvent (water and alcohols with 4 or fewer carbon atoms). The mixing method is not particularly limited and can be done according to conventional methods.
[0072] Amorphous silica dispersions are more stable with less water and more organic solvent, and titanium oxide nanoparticle dispersions are more stable with more water and less organic solvent. Therefore, each can be prepared with a stable solvent ratio, and in this process, the solvent can be added as needed to achieve a preferred solvent ratio while mixing to obtain a preferred SiO2 / TiO2 equivalent mass ratio.
[0073] Regarding the mixing order of the amorphous silica dispersion, the titanium oxide nanoparticle dispersion, and the solvent, it is preferable to dilute the amorphous silica dispersion and the titanium oxide nanoparticle dispersion to their maximum extent to match the final composition before mixing the two liquids. This is because irreversible precipitation may occur if amorphous silica and titanium oxide come into contact in a concentrated state.
[0074] The mixing ratio of the coating solution of the present invention and the titanium oxide dispersion during mixing is not particularly limited, but as described above, it is preferable to adjust the mixing ratio of amorphous silica and titanium oxide nanoparticles to 0.1 to 1.0 (preferably 0.2 to 0.8, more preferably 0.25 to 0.75) in terms of SiO2 / TiO2 mass ratio.
[0075] (3. Uses of coating liquid) The coating liquid of the present invention exhibits excellent dispersibility, hardens at low temperatures, maintains transparency, and has excellent crack resistance and adhesion, enabling dense coatings. It is useful as a coating film when applied to various substrates (glass substrates, metal substrates (stainless steel substrates, aluminum substrates, etc.), resin substrates (polyethylene terephthalate substrates, polycarbonate substrates, polymethyl methacrylate substrates, polyethylene substrates, polyvinyl chloride substrates, etc.), ceramic substrates (alumina substrates, etc.)).
[0076] The coating liquid of the present invention exhibits excellent dispersibility, hardens at low temperatures, maintains transparency, does not impair the photocatalytic effect, has excellent crack resistance and adhesion, and maintains excellent stability over time even when mixed with an aqueous dispersion. Therefore, it enables dense coating and is useful as a photocatalyst when applied to various substrates (glass substrates, metal substrates (stainless steel substrates, aluminum substrates, etc.), resin substrates (polyethylene terephthalate substrates, polycarbonate substrates, polymethyl methacrylate substrates, polyethylene substrates, polyvinyl chloride substrates, etc.), ceramic substrates (alumina substrates, etc.)).
[0077] In particular, when used as an antibacterial agent, antiviral agent, antifungal agent, or deodorant, conventional titanium oxides and organic compounds are expected to detach from the substrate, making the coating of the present invention, which has good adhesion, useful.
[0078] When applied to various substrates, the viscosity of the coating liquid of the present invention can be adjusted according to the application. For example, a low viscosity is preferable when used for spin coating, dip coating, or spraying; a higher viscosity is preferable when used for brush coating or squeegeeing; and an even higher viscosity is preferable when used for screen printing to suppress fluidity. After coating, the coating may be heated to approximately 50-550°C as needed. Higher heating temperatures improve adhesion to the substrate, but the temperature should be determined considering the heat resistance of the substrate.
[0079] Although embodiments of the present invention have been described above, the present invention is not limited in any way to these examples, and can be implemented in various forms without departing from the spirit of the invention. [Examples]
[0080] The embodiments of the present invention will be described in more detail below based on examples, but the present invention is not limited to these.
[0081] The titania sol used in the examples was prepared by the following method. 142.1 g (0.5 mol) of titanium tetraisopropoxide was mixed with 120 g (2 mol) of acetic acid and stirred for 60 minutes. 538 g of water was then added to obtain a dispersion. The dispersion had a titanium tetraisopropoxide concentration of 0.625 mol / L, an acetic acid concentration of 2.5 mol / L, and a pH of 2.2. A translucent precipitate formed, but after stirring for 60 minutes and heating, the precipitate completely dissolved at 70°C, resulting in a dispersed state in the liquid. In this dispersion, the concentrations of inorganic acid, and the elements N, Cl, and S, were all 0 mol / L.
[0082] Subsequently, the mixture was stirred at atmospheric pressure (0.10 MPa) at 98°C for 3 hours, then cooled and left to stand for 1 month. A translucent, homogeneous titania sol was obtained without the use of an organic dispersant. When ultrasonic dispersion was applied to this titania sol, its viscosity decreased and its transparency increased. The heating residue of the obtained titania sol (at 200°C) was 5.7% by mass. The heating residue (at 700°C) was 5.0% by mass. Therefore, the TiO2 equivalent concentration of the obtained liquid can be determined to be 5.0% by mass.
[0083] The resulting titania sol dispersion was dried to obtain titanium oxide nanoparticles (titania nanoparticles), and the BET specific surface area was 265 m². 2 The particle size was [value] / g, the average particle size observed by TEM was approximately 3 nm, and crystallinity analysis by X-ray diffraction revealed that it was 100% anatase type (no other crystalline forms were present).
[0084] Furthermore, the TG-DTA of titanium oxide nanoparticles (titania nanoparticles) obtained by drying the titania sol at 200°C using a moisture meter until the mass loss rate disappeared was measured by raising the temperature to 600°C under an air atmosphere at a rate of 3°C / min. The mass loss rate above 200°C was 12.5% by mass. This mass loss rate above 200°C mainly corresponds to the mass loss rate due to the elimination of acetic acid. Since the liberated acetic acid almost completely volatilizes below 200°C, the 12.5% mass rate above 200°C suggests that a large number of acetylethoxy groups are bonded to the titanium atoms in the form of -OCOCH3 in the titanium oxide nanoparticles.
[0085] Next, the obtained titania sol was diluted with water to prepare a dispersion containing titanium oxide nanoparticles with a TiO2 equivalent concentration of 2.0% by mass (hereinafter referred to as A).
[0086] Furthermore, the mass loss rate for silica-based materials (amorphous silica) was calculated using the value obtained after drying at 200°C and then heating at 600°C. This mass loss rate represents the ratio of terminal organic groups.
[0087] (Example 1) Amorphous silica (18% by mass, mass loss rate 33.3% by mass, residual acid content 0.085% by mass, average particle size 20 nm) was diluted with ethanol to obtain a 2% by mass dispersion (B1). A:B1:ethanol was mixed in a ratio of 1:0.5:0.5 to obtain a translucent dispersion containing 1.0% by mass titania and 0.5% by mass silica. No gelation was observed in the solution after 24 hours. This dispersion was dropped onto an aluminum dish and dried at room temperature for 336 hours, resulting in a transparent coating with slight haze. A friction test using a cotton swab was performed on this coating, and no scratches or peeling were observed. Furthermore, this dispersion was applied to the inside of a 20 mL glass container and dried at 100°C for 1 hour, resulting in a transparent coating on the inside. This glass container was then divided into 4 × 10⁻⁶ -4 When filled with a mass% methylene blue solution and irradiated with ultraviolet light, the coating remained transparent, and even though the irradiation was performed from the back of the glass, the methylene blue decomposed in 40 minutes, resulting in a clear liquid.
[0088] (Example 2) Amorphous silica (10 mass%, mass reduction rate 32.8 mass%, residual acid content 0.025 mass%, average particle diameter 20 nm) was diluted with ethanol to obtain a 2 mass% dispersion (B2). A:B2:ethanol were mixed at a ratio of 1:0.5:0.5 to obtain a translucent dispersion containing 1.0 mass% of titania and 0.5 mass% of silica. No gelation was observed in the liquid even after 24 hours. This dispersion was added dropwise onto an aluminum dish and dried at normal temperature for 336 hours, whereby a transparent coating film was obtained. When a friction test using a cotton swab was performed on this coating film, no scratches or peeling were observed. Further, this dispersion was applied to the inner side of a 20 mL glass container and dried at 100°C for 1 hour, whereby the inner side was coated with a transparent coating film. This glass container was filled with 4×10 -4 mass% methylene blue solution, and when irradiated with ultraviolet light, the methylene blue decomposed in 30 minutes to form a transparent liquid because the coating film was transparent.
[0089] (Example 3) Amorphous silica (20 mass%, mass reduction rate 9.3 mass%, average particle diameter 12 nm) was diluted with ethanol to obtain a 2 mass% dispersion (B3). A:B3:ethanol were mixed at a ratio of 1:0.5:0.5 to obtain a slightly cloudy translucent dispersion containing 1.0 mass% of titania and 0.5 mass% of silica. No gelation was observed in the liquid even after 24 hours. This dispersion was added dropwise onto an aluminum dish and dried at normal temperature for 336 hours, whereby a transparent coating film with slight haze was obtained. When a friction test using a cotton swab was performed on this coating film, no scratches or peeling were observed. This dispersion was applied to the inner side of a 20 mL glass container and dried at 100°C for 1 hour, whereby the inner side was coated with a translucent coating film. This glass container was filled with 4×10 -4 mass% methylene blue solution, and when irradiated with ultraviolet light, the methylene blue decomposed in 45 minutes to form a transparent liquid.
[0090] (Example 4) The test was carried out in the same manner as in Example 2, except that A:B2 was mixed in a 1:1 ratio to obtain a translucent dispersion containing 1.0% by mass of titania and 1.0% by mass of silica. No gelation was observed in the solution after 24 hours. When this dispersion was dropped onto an aluminum dish and dried at room temperature for 336 hours, a nearly transparent coating was obtained. When a friction test was performed on this coating using a cotton swab, no scratches or peeling were observed. When this dispersion was applied to the inside of a 20 mL glass container and dried at 100°C for 1 hour, the inside was coated with a transparent coating. This glass container was then divided into 4 × 10 -4 When a container was filled with a mass% methylene blue solution and irradiated with ultraviolet light, the methylene blue decomposed in 40 minutes, resulting in a clear liquid.
[0091] (Example 5) The test was carried out in the same manner as in Example 2, except that A:B2:ethanol was mixed in a ratio of 1:0.25:0.75 to obtain a translucent dispersion containing 1.0% by mass of titania and 0.25% by mass of silica. No gelation was observed in the solution after 24 hours. This dispersion was dropped onto an aluminum dish and dried at room temperature for 336 hours to obtain a transparent coating. When a friction test was performed on this coating using a cotton swab, no scratches or peeling were observed. This dispersion was applied to the inside of a 20 mL glass container and dried at 100°C for 1 hour to coat the inside with a transparent coating. This glass container was then divided into 4 × 10 -4 When a container was filled with a mass% methylene blue solution and irradiated with ultraviolet light, the methylene blue decomposed in 40 minutes, resulting in a clear liquid.
[0092] (Example 6) The test was carried out in the same manner as in Example 2, except that a translucent dispersion containing 1.0% by mass of titania and 0.1% by mass of silica was obtained by mixing A:B2:ethanol in a ratio of 1:0.1:0.9. No gelation was observed in the solution even after 24 hours. When this dispersion was dropped onto an aluminum dish and dried at room temperature for 336 hours, a transparent coating was obtained. When a friction test was performed on this coating using a cotton swab, slight scratches were observed, but no peeling was seen. When this dispersion was applied to the inside of a 20 mL glass container and dried at 100°C for 1 hour, the inside was coated with a transparent coating. This glass container was then divided into 4 × 10 -4When a container was filled with a mass% methylene blue solution and irradiated with ultraviolet light, the methylene blue decomposed in 40 minutes, resulting in a clear liquid.
[0093] (Example 7) The test was carried out in the same manner as in Example 2, except that A:B2:ethanol was mixed in a ratio of 0.5:1.0:0.5 to obtain a translucent dispersion containing 0.5% by mass of titania and 1.0% by mass of silica. No gelation was observed in the solution even after 24 hours. When this dispersion was dropped onto an aluminum dish and dried at room temperature for 336 hours, a transparent coating was obtained. When a friction test was performed on this coating using a cotton swab, slight scratches were observed, but no peeling was seen. When this dispersion was applied to the inside of a 20 mL glass container and dried at 100°C for 1 hour, the inside was coated with a transparent coating. This glass container was then divided into 4 × 10 -4 When a container was filled with a mass% methylene blue solution and irradiated with ultraviolet light, the methylene blue decomposed in 40 minutes, resulting in a clear liquid.
[0094] (Comparative Example 1) A: Ethanol was diluted 1:1 to obtain a translucent dispersion of titania at 1.0% by mass. No gelation was observed in the solution after 24 hours. This dispersion was dropped onto an aluminum dish and dried at room temperature for 336 hours, resulting in a nearly transparent coating. A friction test using a cotton swab was performed on this coating, and peeling of the coating and cloudy streaks were observed. This dispersion was applied to the inside of a 20 mL glass container and dried at 100°C for 1 hour, resulting in a transparent coating on the inside. This glass container was then divided into 4 × 10⁻⁶ -4 When a container was filled with a mass% methylene blue solution and irradiated with ultraviolet light, the methylene blue decomposed in 35 minutes, resulting in a clear liquid.
[0095] (Comparative Example 2) Silica sol (34% by mass, 4% mass loss rate, average particle size 25 nm) was diluted with ethanol to obtain a 2% by mass dispersion (BR2). A:BR2:ethanol was mixed in a ratio of 1:0.5:0.5 to obtain a cloudy dispersion containing 1.0% by mass titania and 0.5% by mass silane compound. The solution gelled after 10 minutes. This dispersion was dropped onto an aluminum dish before gelling and dried at room temperature for 336 hours to obtain a cloudy coating. A friction test using a cotton swab was performed on this coating, and it peeled off completely. This dispersion was applied to the inside of a 20 mL glass container and dried at 100°C for 1 hour, and some peeling of the coating was observed. This glass container was then divided into 4 × 10⁶ -4 When a container was filled with a mass% methylene blue solution and irradiated with ultraviolet light, it took 50 minutes for the methylene blue to decompose.
[0096] (Comparative Example 3) Methyltrimethoxysilane (mass loss rate 56% by mass) was diluted with ethanol to obtain a 2% by mass dispersion (BR3). A:BR3:ethanol was mixed in a ratio of 1:0.5:0.5 to obtain a translucent dispersion containing 1.0% by mass of titania and 0.5% by mass of the silane compound. No gelation was observed in the solution after 24 hours. This dispersion was dropped onto an aluminum dish before gelation and dried at room temperature for 336 hours to obtain a transparent coating. A friction test using a cotton swab was performed on this coating, and although no peeling occurred, scratches were observed. This dispersion was applied to the inside of a 20 mL glass container and dried at 100°C for 1 hour, resulting in a translucent coating on the inside. This glass container was then divided into 4 × 10⁻⁶ -4 When a container was filled with a mass% methylene blue solution and irradiated with ultraviolet light, it took 50 minutes for the methylene blue to decompose.
[0097] (Comparative Example 4) 3-glycidoxypropyltrimethoxysilane (74% mass loss), a silane coupling agent, was diluted with ethanol to obtain a 2% by mass dispersion (BR4). A:BR4:ethanol was mixed in a ratio of 1:0.5:0.5 to obtain a translucent dispersion containing 1.0% by mass of titania and 0.5% by mass of the silane compound. No gelation was observed after 24 hours. This dispersion was dropped onto an aluminum dish before gelation and dried at room temperature for 336 hours to obtain a transparent coating. A friction test using a cotton swab on this coating did not result in peeling, but scratches were observed. This dispersion was applied to the inside of a 20 mL glass container and dried at 100°C for 1 hour, resulting in a transparent coating on the inside. This glass container was then divided into 4 × 10⁶ -4 When a container was filled with a mass% methylene blue solution and irradiated with ultraviolet light, the decomposition of the methylene blue was not completed even after 50 minutes.
[0098] (Comparative Example 5) Dried silica nanoparticles (fumed silica, average particle size 8 nm) were diluted with ethanol to obtain a 2% by mass turbid dispersion (BR5). A:BR5:ethanol was mixed in a ratio of 1:0.5:0.5 to obtain a turbid dispersion containing 1.0% by mass titania and 0.5% by mass silane compound. Precipitation was observed after 24 hours. This dispersion was dropped onto an aluminum dish before precipitation occurred and dried at room temperature for 336 hours to obtain a turbid coating. A friction test using a cotton swab was performed on this coating, and some peeling occurred, revealing turbid streaks. This dispersion was applied to the inside of a 20 mL glass container and dried at 100°C for 1 hour to obtain a turbid coating. This glass container was then divided into 4 × 10⁻⁶ -4 When a container was filled with a mass% methylene blue solution and irradiated with ultraviolet light, it took 50 minutes for the methylene blue to decompose.
[0099] (Comparative Example 6) As a silica precursor, an alkoxysilane oligomer (mass loss rate 59%) was diluted with ethanol to obtain a 2% by mass dispersion (BR6). A:BR6:ethanol was mixed in a ratio of 1:0.5:0.5 to obtain a cloudy dispersion containing 1.0% by mass of titania and 0.5% by mass of silica. The solution gelled after 16 hours. This dispersion was dropped onto an aluminum dish before gelling and dried at room temperature for 336 hours to obtain a cloudy coating film. When a friction test was performed on this coating film using a cotton swab, cracks appeared and some parts peeled off.
[0100] (Comparative Example 7) Amorphous silica (21% by mass, 37% mass loss, 0.35% residual acid content, average particle size 20 nm) was diluted with ethanol to obtain a 2% by mass dispersion (BR7). A:BR7:ethanol was mixed in a ratio of 1:0.5:0.5 to obtain a translucent dispersion containing 1.0% by mass titania and 0.5% by mass silica, which gelled after 24 hours. This dispersion was dropped onto an aluminum dish and dried at room temperature for 336 hours, resulting in a cloudy coating. A friction test using a cotton swab was performed on this coating, and no scratches or peeling were observed.
[0101] Thus, by using amorphous silica with terminal organic groups within a certain range, transparency, liquid stability, coating strength, and photocatalytic properties can be achieved simultaneously. Since the coatings formed in each example have a fine porous structure, the decomposition rate of methylene blue was higher than when a dense coating of titania alone was formed.
[0102] On the other hand, when silica with few terminal organic groups was used, the strength of the coating film was insufficient, possibly due to insufficient adhesion between titania and silica, and between silica and the substrate. Conversely, when silica or silica precursors with too many terminal organic groups were used, the stability of the liquid and the transparency of the coating film tended to be insufficient, possibly due to the reaction between titania and silica being too fast or the bond being too strong.
[0103] (Experimental Example 8, Comparative Example 8) 5% by mass of Ag nanoparticles relative to titania were supported in the dispersions of Example 2 and Comparative Example 1, and further diluted five times with water to obtain the antiviral agent of Example 8 and the antiviral agent of Comparative Example 8, respectively, and applied to drawing paper at a density of 60 g / m². 2 I painted it with a brush.
[0104] After drying, an antiviral test was performed in the dark using Qβ phage (non-enveloped virus) in accordance with ISO 21702. As a result, the antiviral activity of the antiviral agent in Example 8 was 2.1, and the antiviral activity of the antiviral agent in Comparative Example 8 was 1.7. Example 8 showed superior antiviral activity compared to Comparative Example 8 and exceeded the standard value of 2.0 (99% inactivation) which indicates general antiviral activity.
Claims
1. A product containing 100% anatase-type titanium oxide nanoparticles, amorphous silica, water, and alcohols having 4 or fewer carbon atoms, The titanium oxide nanoparticles have acetoxy groups bonded to their surface, exhibit a mass loss rate of 5% or more at temperatures above 200°C when heated to 600°C using a differential thermogravimetric analyzer, and have an average particle diameter of 1 to 10 nm. The amorphous silica is characterized in that it has a residual acid content of 100 ppm or less, a residual alkoxy group content of 5 to 35% by mass, and an average particle diameter of 50 nm or less, as a coating solution.
2. The mass (M) of the titanium oxide nanoparticles T Amorphous silica mass (M) relative to ) A ) Mass ratio (M A / M T The coating liquid according to claim 1, wherein the ratio is 0.1 to 2.
0.
3. The aforementioned alcohols are at least one selected from the group consisting of methanol, ethanol, 1-propanol, 2-propanol, 2-butanol, and tert-butyl alcohol. The coating liquid according to claim 1 or 2, wherein the mass of water contained in the coating liquid is 10 to 60% by mass, with the total mass of the water and alcohols being 100% by mass.
4. A coating film formed by the coating liquid according to any one of claims 1 to 3.
5. An antimicrobial or antiviral agent manufactured using the coating liquid described in any one of claims 1 to 3.
Citation Information
Patent Citations
Production of hydrophilic coating
JP2000001340A
Composite material having photocatalytic hydrophilic surface
JP2000075114A
Method of photocatalytically making the surface of base material ultrahydrophilic, base material having ultrahydrophilic and photocatalytic surface, and process for producing said material
WO1996029375A1